2021
DOI: 10.3892/etm.2021.9851
|View full text |Cite
|
Sign up to set email alerts
|

Effect of TNF‑α on the proliferation and osteogenesis of human periodontal mesenchymal stem cells

Abstract: The aim of the present study was to investigate the effect of tumor necrosis factor-α (TNF-α) on the proliferation and osteogenesis of human periodontal mesenchymal stem cells (hPDLSCs). Antigen expression in hPDLSCs was detected by flow cytometry. hPDLSCs were divided into four groups: A control group with no TNF-α treatment, and three experimental groups treated with 0.1, 1 and 10 ng/ml TNF-α, respectively. The effect of TNF-α on proliferation of hPDLSCs in vitro was detected using a C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…PDLSCs are regarded as the main functional cells for periodontal tissue repair and regeneration, which are influenced by macrophage polarization. However, in periodontitis, the osteogenic capacity of PDLSCs was severely impaired due to inflammatory cytokines [ 44 ]. Prior studies showed that the CM of M2 macrophages promoted PDLSC osteogenic and cementoblastic differentiation through Akt and JNK signaling [ 45 ], while the CM of M1 macrophages impaired osteogenesis [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…PDLSCs are regarded as the main functional cells for periodontal tissue repair and regeneration, which are influenced by macrophage polarization. However, in periodontitis, the osteogenic capacity of PDLSCs was severely impaired due to inflammatory cytokines [ 44 ]. Prior studies showed that the CM of M2 macrophages promoted PDLSC osteogenic and cementoblastic differentiation through Akt and JNK signaling [ 45 ], while the CM of M1 macrophages impaired osteogenesis [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…This research analyzed the effects of vitamin D on the osteogenic differentiation and mineralization of human mesenchymal stem cells. Differentiation into an osteogenic lineage was detected by alkaline phosphatase activity, and the mRNA levels of RUNX2, BSP, OCN, and COL1A1 were detected using real-time quantitative polymerase chain reaction [26].…”
Section: Discussionmentioning
confidence: 99%
“…This secondary damage can include a prolonged inflammatory response, increased permeability of the blood-brain barrier, cytotoxicity, apoptosis, excitotoxity, and demyelination ( Kuno et al, 2005 ), all of which prolong microglial reactivity ( Smith et al, 2012 ). TNF-α is also involved with signaling pathways that control cell division in a variety of cell types ( Cao et al, 2021 ; Niu et al, 2021 ; Skartsis et al, 2021 ). We hypothesized that eliminating TNF-α from microglia by genetic knockout (KO) would reduce microglial cell division and activation following an inflammatory trigger.…”
Section: Introductionmentioning
confidence: 99%